Corporate Governance and Financial Distress: Empirical Evidence from Transportation and Logistics Sector - Ainul Fitri (CV. Civiliza Publishing, 2025)
This study investigates the role of corporate governance mechanisms in reducing financial distress among transportation and logistics companies listed on the Indonesia Stock Exchange (IDX). Motivated by the sector’s high capital intensity, operational complexity, and vulnerability to economic shocks, the research analyzes how institutional ownership, independent board of commissioners, and audit committee structures influence firms’ financial stability. Using an explanatory quantitative approach, the study employs panel data from 18 publicly listed transportation and logistics firms over the 2021-2024 period, yielding 72 firm-year observations. Financial distress is measured using the Altman Z-Score for emerging markets, while governance variables are obtained from annual reports and corporate governance disclosures. Panel data regression with a Fixed Effect Model (FEM) is applied, preceded by classical assumption and model specification tests. The results show that institutional ownership, independent board of commissioners, and audit committee all have a significant negative effect on financial distress, indicating that stronger governance practices are associated with lower likelihood of financial failure. These findings provide theoretical support for Agency and Stewardship Theory, and offer practical implications for regulators, investors, and corporate boards in strengthening governance frameworks within high-risk, capital-intensive industries.